Risk factors associated with the seroprevalence of Neospora caninum in naturally infected bovine in the tropical highlands of Oxapampa, Peru - Portocarrero M., Carlos (2015)
The aim of the present study was to determine the risk factors associated with the seroprevalence ofNeospora caninum in naturally infected bovine in the tropical highlands of Oxapampa, Peru. The study was carried out in 20 herds in Chontabamba and Oxapampa districts. Blood samples were collected from 388 animals older than 6 months of age, and a survey was conducted to identify potential risk factors in the herds. The presence of antibodies against N. caninum was done by the c-ELISA test using a commercial kit. The association between seroprevalence of N. caninum and the variables evaluated (age group, origin, herd size, disposal of animal remains, number of dogs per herd) were analyzed by the logistic regression. The seroprevalence ofN. caninum was 18.8 ± 3.9%. The risk factors associated with seroprevalence ofN. caninum in bovine were the presence of more than three dogs in the herd, the disposal of animal remains in the environment and a herd size larger than 10 animals (p<0.05), whereas age and origin did not influence the presence of N. caninum.